A cement adhesive and its preparation method and application
By adding carbon nanotubes and sodium chloride to the cement glue and adopting a composite curing system, the problem of poor electrical performance of existing cement glue is solved, and the stability and electrical performance of porcelain insulators are significantly improved.
Patent Information
- Application Number
- CN202411569788.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing cement adhesives have poor electrical performance under high electric field conditions, making it difficult to ensure the safe and stable operation of porcelain insulators when facing steep wave impact voltages.
Use cement glue with aluminate cement, artificial porcelain sand, microsilicon powder, carbon nanotubes and sodium chloride, and improve the electrical energy of the glue through a composite maintenance system of static stop, steaming and standard water maintenance. performance.
The electrical and mechanical properties of cement adhesives are significantly improved, ensuring the stable operation of porcelain insulators under high electric field conditions, and the impact breakdown test pass rate reaches more than 0.999.
Smart Images

Figure CN119059782B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement adhesives, and in particular relates to a cement adhesive and a preparation method and application thereof. Background Art
[0002] Porcelain insulators in power systems play an important role in electrical insulation, supporting transmission lines and equipment and preventing electrical failures of power equipment due to the influence of the external environment. Therefore, research on the fixing methods and materials of porcelain insulators is crucial to ensure the safe and stable operation of power systems.
[0003] The cement adhesive of porcelain insulators has a very important influence on the performance of porcelain insulators. When cement adhesives are used in strong electric fields, they may be subjected to impulse voltages. Therefore, it is necessary to improve the electrical properties of cement adhesives to ensure that porcelain insulators can still operate safely and stably when facing steep wave impulse voltages. However, the electrical properties of current cement adhesives are relatively poor. Therefore, how to improve the electrical properties of cement adhesives to ensure that porcelain insulators can still operate safely and stably when facing steep wave impulse voltages has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a cement adhesive and a preparation method and application thereof. The cement adhesive provided by the present invention can improve the electrical performance of the cement adhesive and ensure that the porcelain insulator can still operate safely and stably when facing steep wave impulse voltage.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, microsilica powder, an admixture and water;
[0007] The external admixture includes carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent;
[0008] The water reducer is a polycarboxylate water reducer.
[0009] Preferably, the mass of the aluminate cement is 45-62% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder.
[0010] Preferably, the mass of the artificial porcelain sand is 25~45% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the mass of the microsilica powder is 5~10% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder.
[0011] Preferably, the mass of the carbon nanotubes is 0.03-0.05% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder.
[0012] Preferably, the mass of the sodium chloride is 0.1-0.3% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder.
[0013] Preferably, the water-cement ratio of the cement adhesive is 0.20-0.25.
[0014] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:
[0015] Aluminate cement, artificial porcelain sand, microsilica powder, admixtures and water are mixed to obtain cement adhesive.
[0016] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.
[0017] Preferably, the application method comprises:
[0018] The cement adhesive is poured into the anti-pollution porcelain insulators in high-cold areas, and then static curing, steam curing and standard water curing are carried out in sequence.
[0019] Preferably, the static time is 4-5 hours; the steaming temperature is 45-55° C., and the steaming time is 5-6 hours.
[0020] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, microsilica powder, an admixture and water; the admixture comprises carbon nanotubes, sodium chloride, a water reducer and a defoamer; the water reducer is a polycarboxylic acid water reducer. In the present invention, carbon nanotubes and sodium chloride can synergistically improve the electrical properties of the cement adhesive, wherein the synergistic effect of carbon nanotubes and sodium chloride in the cement adhesive is mainly reflected in improving the electrical conductivity; carbon nanotubes as conductive fillers can significantly improve the electrical conductivity of the cement matrix; and sodium chloride promotes the solidification and hardening of cement, providing a better dispersion and bonding environment for carbon nanotubes, thereby helping to form a more stable conductive network, while the coagulant effect of sodium chloride helps to improve the dispersion and interfacial bonding of carbon nanotubes in the cement matrix, thereby optimizing the piezoresistive effect of the cement adhesive. Experimental results show that the pass rate of the impact breakdown test of the cement adhesive provided by the present invention after 28 days of curing is above 0.999. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2;
[0022] Figure 2 is the flexural strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2;
[0023] Figure 3is the compression ratio of the cement adhesive prepared in Example 1 and Comparative Examples 1-2;
[0024] Figure 4 The compressive strength of the cement adhesive after curing in Application Example 1 and Comparative Application Examples 1 to 3;
[0025] Figure 5 The flexural strength of the cement adhesive after curing in Application Example 1 and Comparative Application Examples 1 to 3;
[0026] Figure 6 The impact breakdown test pass rate data of the cement adhesives prepared in Example 1 and Comparative Examples 4 to 6 after curing for 28 days. DETAILED DESCRIPTION
[0027] The present invention provides a cement adhesive, comprising the following components: aluminate cement, artificial porcelain sand, microsilica powder, an admixture and water;
[0028] The external admixture includes carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent;
[0029] The water reducer is a polycarboxylate water reducer.
[0030] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0031] In the present invention, the cement binder comprises aluminate cement; the aluminate cement is preferably CA50-II. In the present invention, the aluminate cement is a matrix material.
[0032] In the present invention, the cement adhesive further comprises artificial porcelain sand; the particle size of the artificial porcelain sand is preferably 0.3-2 mm. In the present invention, the artificial porcelain sand has better particle distribution and filling performance, can improve the density and strength of cement, reduce pores and defects in cement, and improve the durability and crack resistance of cement.
[0033] In the present invention, the cement binder further comprises microsilica fume; the particle size of the microsilica fume is preferably 0.1-0.3 μm; the content of SiO2 in the microsilica fume is preferably ≥93wt%. In the present invention, the microsilica fume has a significant effect of improving the microstructure of hardened cement paste and concrete.
[0034] Taking the total mass of aluminate cement, artificial porcelain sand and microsilica as 100%, the mass content of aluminate cement is preferably 45-62%; the mass content of artificial porcelain sand is preferably 25-45%; the mass content of microsilica is preferably 5-10%. In the present invention, limiting the content of aluminate cement, artificial porcelain sand and microsilica within the above range can further improve the electrical properties of cement adhesive, while improving compressive strength and flexural strength, and reducing shrinkage and water usage.
[0035] As an implementation mode, based on the total mass of aluminate cement, artificial porcelain sand and microsilica fume as 100%, the mass content of the aluminate cement may be 50~60%, or 55%; the mass content of the artificial porcelain sand may be 30~40%, or 35~40%; the mass content of the microsilica fume may be 5~8%.
[0036] In the present invention, the cement binder also includes an admixture; the admixture includes carbon nanotubes and sodium chloride. In the present invention, the synergistic effect of carbon nanotubes and sodium chloride in the cement binder is mainly reflected in improving electrical conductivity; carbon nanotubes, as conductive fillers, can significantly improve the electrical conductivity of the cement matrix; and sodium chloride promotes the solidification and hardening of cement, providing a better dispersion and bonding environment for carbon nanotubes, thereby helping to form a more stable conductive network, while the coagulant effect of sodium chloride helps to improve the dispersion and interfacial bonding of carbon nanotubes in the cement matrix, thereby optimizing the piezoresistive effect of the cement binder, so that the cement binder can more accurately reflect stress changes when subjected to pressure.
[0037] In the present invention, the mass of the carbon nanotubes is preferably 0.03-0.05% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the diameter of the carbon nanotubes is preferably 10-20 nm. In the present invention, the carbon nanotubes can improve the electrical conductivity of cement, and the carbon nanotubes can also fill the pores in cement to increase the strength of cement adhesive, and can synergistically improve the electrical properties of cement adhesive with sodium chloride.
[0038] As an implementation mode, the mass of the carbon nanotubes may be 0.03-0.04% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder.
[0039] In the present invention, the mass of the sodium chloride is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder. In the present invention, the sodium chloride can improve the fluidity of cement and synergistically improve the electrical properties of cement binder with carbon nanotubes; limiting the mass of sodium chloride within the above range can further improve the electrical properties of cement binder.
[0040] In the present invention, the external admixture further includes a water reducing agent and a defoaming agent.
[0041] In the present invention, the water reducer is a polycarboxylate water reducer; the mass of the water reducer is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder. In the present invention, the polycarboxylate water reducer can enable the cement adhesive to still exert a good water reduction effect under low temperature conditions and accelerate the solidification and curing process of cement.
[0042] In the present invention, the water reducer is preferably a polycarboxylic acid water reducer with acrylic acid / methacrylic acid as the main chain or a polycarboxylic acid water reducer with maleic anhydride as the main chain.
[0043] As an implementation mode, the mass of the water reducing agent can be 0.1-0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder.
[0044] In the present invention, the defoamer is preferably a silicone oil defoamer; the mass of the defoamer is preferably 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder. In the present invention, the defoamer effectively reduces bubbles and foam on the surface of cement slurry, reduces the formation of pores, and improves the density and quality of cement adhesive.
[0045] As an implementation mode, the mass of the defoaming agent can be 0.1-0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder.
[0046] In the present invention, the cement binder further comprises water; the water-cement ratio of the cement binder is preferably 0.20 to 0.25. In the present invention, the water is a solvent.
[0047] As an implementation mode, the water-cement ratio may be 0.22-0.24.
[0048] In the present invention, the carbon nanotubes and sodium chloride can synergistically improve the electrical properties of the cement binder, wherein the synergistic effect of the carbon nanotubes and sodium chloride in the cement binder is mainly reflected in improving the electrical conductivity; the carbon nanotubes as conductive fillers can significantly improve the electrical conductivity of the cement matrix; and the sodium chloride promotes the solidification and hardening of the cement, thereby providing a better dispersion and bonding environment for the carbon nanotubes, thereby helping to form a more stable conductive network, and at the same time, the coagulant effect of the sodium chloride helps to improve the dispersion and interfacial bonding force of the carbon nanotubes in the cement matrix, thereby optimizing the piezoresistive effect of the cement binder.
[0049] The present invention adopts polycarboxylic acid to replace the naphthalene-based water reducer. Polycarboxylic acid is a high-efficiency water reducer. Compared with the traditional naphthalene-based water reducer, the molecular structure of the polycarboxylic acid is more stable and the dispersibility and adsorption are higher. Under natural curing conditions, the use of polycarboxylic acid as a water reducer can more effectively promote the dispersion and bonding between cement particles, thereby improving the density and uniformity of the cement binder. Therefore, the performance of the cement binder is significantly improved in terms of compressive strength and flexural strength. In addition, due to the action mechanism of the polycarboxylic acid water reducer, the surface tension of the cement paste can be effectively reduced, and the increase of the shrinkage rate is suppressed, thereby reducing the shrinkage rate of the cement binder and improving its stability and durability.
[0050] The defoamer added in the present invention has a significant impact on the microstructure and performance of the cement adhesive; the function of the defoamer is to reduce the surface tension of the liquid and inhibit the generation and stability of bubbles or foams; therefore, adding an appropriate amount of defoamer to the cement adhesive can effectively reduce the formation of pores and foams, and improve the density and uniformity of the cement adhesive; through high-power optical microscope observation, it can be clearly seen that the number and size of pores in the cement adhesive are reduced, further improving the strength and stability of the cement adhesive.
[0051] The present invention also provides a method for preparing the cement adhesive described in the above technical solution, comprising:
[0052] Aluminate cement, artificial porcelain sand, microsilica powder, admixtures and water are mixed to obtain cement adhesive.
[0053] The present invention has no special limitation on the mixing operation of the aluminate cement, artificial porcelain sand, microsilica powder, admixture and water, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0054] The preparation method provided by the invention has simple process and is suitable for industrial production.
[0055] The present invention also provides the use of the cement adhesive described in the above technical solution or the cement adhesive prepared by the preparation method described in the above technical solution in anti-pollution porcelain insulators in high-cold areas.
[0056] In the present invention, the application method preferably includes:
[0057] The cement adhesive is poured into the anti-pollution porcelain insulators in high-cold areas, and then static curing, steam curing and standard water curing are carried out in sequence.
[0058] The present invention has no special limitation on the pouring operation, and operations well known to those skilled in the art may be adopted.
[0059] In the present invention, the static time is preferably 4-5 hours; the steam curing temperature is preferably 45-55°C; and the steam curing time is preferably 5-6 hours. The present invention changes the curing system and adopts static, steam and water curing, which can promote the hydration reaction of cement particles faster, improve the density and strength of cement adhesive, and especially improve the flexural strength of cement adhesive. This curing method has obvious effect; the curing method provided by the present invention enables cement adhesive to better adapt to the special environment of high-cold areas, ensures its stability and reliability under extreme low temperature conditions, and provides important technical support for the construction of engineering fields such as power systems in cold areas. At the same time, facing impulse voltage, it can ensure stable and safe operation.
[0060] The present invention has no special limitation on the operation of the standard water curing. The operation familiar to those skilled in the art can be adopted, and the standard constant temperature water can be used for curing until the age.
[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] Example 1
[0063] The components of cement adhesive are: aluminate cement, artificial porcelain sand, microsilica powder, admixture and water;
[0064] The external admixtures are carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent;
[0065] The mass of the aluminate cement is 55% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder, and the model is CA50-Ⅱ;
[0066] The mass of the artificial porcelain sand is 40% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder, and the particle size is 0.3-2 mm;
[0067] The mass of the microsilica fume is 5% of the total mass of aluminate cement, artificial porcelain sand and microsilica fume, the particle size is 0.1-0.3 μm, and the content of SiO2 in the microsilica fume is 98wt%;
[0068] The mass of the carbon nanotubes is 0.04% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the diameter of the carbon nanotubes is 10-20 nm;
[0069] The mass of the sodium chloride is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0070] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0071] The defoamer is P803 silicon cement mortar defoamer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0072] The water-cement ratio of the cement binder is 0.23;
[0073] The preparation method of the cement adhesive is:
[0074] Aluminate cement, artificial porcelain sand, microsilica powder, carbon nanotubes and sodium chloride are mixed, and after mixing, a water reducer and a defoamer are added, and then water is added and stirred for 10 minutes to obtain a cement adhesive.
[0075] Comparative Example 1
[0076] On the basis of Example 1, the type of water reducer was changed to water reducer FDN-A, and other conditions remained unchanged.
[0077] Comparative Example 2
[0078] On the basis of Example 1, the type of water reducer was changed to water reducer FDN-C, and other conditions remained unchanged.
[0079] The cement adhesive prepared in Example 1 and Comparative Examples 1-2 was subjected to performance tests, and the flexural strength, compressive strength, shrinkage rate test, etc. were conducted in accordance with JB / T 4307-2004 "Cement adhesive for insulator assembly"; the fluidity of the cement adhesive was tested in accordance with GB / T 2419-2005 "Method for determination of fluidity of cement mortar", and the results are shown in Tables 1-2 and Figures 1 to 3 As shown; Figure 1 is the compressive strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2, Figure 2 is the flexural strength of the cement adhesive prepared in Example 1 and Comparative Examples 1-2, Figure 3 It is the compression ratio of the cement adhesive prepared in Example 1 and Comparative Examples 1-2.
[0080] Table 1 Performance data of cement adhesives prepared in Example 1 and Comparative Examples 1-2
[0081]
[0082] Table 2 Performance data of cement adhesives prepared in Example 1 and Comparative Examples 1-2
[0083]
[0084] From Table 1~2 and Figures 1 to 3It can be seen that under natural curing, the technical solution of the present invention using a high-efficiency water-reducing agent has significantly improved strength, with the 28-day compressive and flexural strengths increased by 41% and 70% respectively; the high water reduction rate of the high-efficiency water-reducing agent can reduce the initial water consumption, so that the 28-day shrinkage rate is also reduced by 23.4%.
[0085] Application Example 1
[0086] The cement adhesive prepared in Example 1 was poured into the anti-pollution porcelain insulators for high-cold areas, and then sequentially subjected to 4h of static curing, 6h of steam curing at 50°C, and standard constant temperature water curing until the insulators reached the age.
[0087] Comparative application example 1
[0088] Based on Application Example 1, the static stop is omitted and the standard constant temperature water curing is modified to being placed in the air to reach the age, and other conditions remain unchanged.
[0089] Comparative Application Example 2
[0090] Based on Application Example 1, the standard constant temperature water curing is modified to placing in the air until the age, and other conditions remain unchanged.
[0091] Comparative Application Example 3
[0092] Based on Application Example 1, the static stop is omitted and other conditions remain unchanged.
[0093] According to the test method of Example 1, the performance test of the cement adhesive after curing of Example 1 and Comparative Application Examples 1 to 3 was carried out. The results are shown in Table 3 and Figures 4 and 5 As shown, Figure 4 The compressive strength of the cement adhesive after curing in Application Example 1 and Comparative Application Examples 1 to 3 is shown in Figure 2. Figure 5 It is the flexural strength of the cement adhesive after curing in Application Example 1 and Comparative Application Examples 1 to 3.
[0094] Table 3 Performance data of cement adhesive after curing of application example 1 and comparative application examples 1 to 3
[0095]
[0096] From Table 3 and Figures 4 and 5 It can be seen that static treatment can improve the compressive strength of cement adhesive (up to about 15.9MPa), steaming and water curing can improve the flexural strength of cement adhesive (up to about 7.4MPa), and improve the strength decline in the middle and late stages; the composite curing system of the present invention is conducive to comprehensively improving the compressive and flexural properties of cement adhesive.
[0097] Example 2
[0098] On the basis of Example 1, the content of the defoaming agent was modified to 0.3%, and other conditions remained unchanged.
[0099] Comparative Example 3
[0100] The defoamer was omitted on the basis of Example 2, and other conditions remained unchanged.
[0101] The cement adhesive prepared in Example 2 and Comparative Example 3 was poured into the anti-pollution porcelain insulator for high-cold areas, and then sequentially stopped for 4 hours, steamed at 50°C for 6 hours, and cured in standard constant temperature water for 28 days, and then tested according to standard DL / T 557-2021 to obtain the impact breakdown test pass rate; the performance test was carried out according to the test method of Example 1, and the results are shown in Table 4.
[0102] Table 4 Performance data of cement adhesives prepared in Example 2 and Comparative Example 3 after curing
[0103]
[0104] It can be seen from Table 4 that the cement adhesive of the present invention has excellent electrical and mechanical properties.
[0105] Comparative Example 4
[0106] Based on Example 1, sodium chloride and carbon nanotubes were omitted, and other conditions remained unchanged.
[0107] Comparative Example 5
[0108] On the basis of Example 1, the carbon nanotubes were omitted, the mass of sodium chloride was modified to 0.24%, and other conditions remained unchanged.
[0109] Comparative Example 6
[0110] Based on Example 1, sodium chloride was omitted, the mass of carbon nanotubes was modified to 0.24%, and other conditions remained unchanged.
[0111] The cement adhesive prepared in Example 1 and Comparative Examples 4 to 6 was poured into the anti-pollution porcelain insulator in the high-cold area, and then left to stand for 4 hours, steamed at 50°C for 6 hours, and cured in standard constant temperature water for 28 days, and then tested according to standard DL / T 557-2021, and the impact breakdown test pass rate was obtained as follows: Figure 6 shown.
[0112] from Figure 6 It can be seen that the use of sodium chloride and carbon nanotubes can significantly improve the steep wave performance of cement adhesive.
[0113] Example 3
[0114] The components of cement adhesive are: aluminate cement, artificial porcelain sand, microsilica powder, admixture and water;
[0115] The external admixtures are carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent;
[0116] The mass of the aluminate cement is 45% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder, and the model is CA50-Ⅱ;
[0117] The mass of the artificial porcelain sand is 45% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder, and the particle size is 0.3-2 mm;
[0118] The mass of the microsilica fume is 10% of the total mass of aluminate cement, artificial porcelain sand and microsilica fume, the particle size is 0.1-0.3 μm, and the content of SiO2 in the microsilica fume is 98wt%;
[0119] The mass of the carbon nanotubes is 0.03% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the diameter of the carbon nanotubes is 10-20 nm;
[0120] The mass of the sodium chloride is 0.3% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0121] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0122] The defoamer is P803 silicon cement mortar defoamer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0123] The water-cement ratio of the cement adhesive is 0.20;
[0124] The preparation method of the cement adhesive is:
[0125] Aluminate cement, artificial porcelain sand, microsilica powder, carbon nanotubes and sodium chloride are mixed, and after mixing, a water reducer and a defoamer are added, and then water is added and stirred for 10 minutes to obtain a cement adhesive.
[0126] Example 4
[0127] The components of cement adhesive are: aluminate cement, artificial porcelain sand, microsilica powder, admixture and water;
[0128] The external admixtures are carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent;
[0129] The mass of the aluminate cement is 62% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder, and the model is CA50-Ⅱ;
[0130] The mass of the artificial porcelain sand is 30% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder, and the particle size is 0.3-2 mm;
[0131] The mass of the microsilica fume is 8% of the total mass of aluminate cement, artificial porcelain sand and microsilica fume, the particle size is 0.1-0.3 μm, and the content of SiO2 in the microsilica fume is 98wt%;
[0132] The mass of the carbon nanotubes is 0.05% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the diameter of the carbon nanotubes is 10-20 nm;
[0133] The mass of the sodium chloride is 0.1% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0134] The water reducer is TS-JS (I) polycarboxylic acid high-performance water reducer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0135] The defoamer is P803 silicon cement mortar defoamer, and its mass is 0.2% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder;
[0136] The water-cement ratio of the cement binder is 0.25;
[0137] The preparation method of the cement adhesive is:
[0138] Aluminate cement, artificial porcelain sand, microsilica powder, carbon nanotubes and sodium chloride are mixed, and after mixing, a water reducer and a defoamer are added, and then water is added and stirred for 10 minutes to obtain a cement adhesive.
[0139] The performance of the cement adhesive prepared in Examples 3 and 4 was tested according to the testing method of Example 1. The results are shown in Tables 5 and 6.
[0140] Table 5 Performance data of cement adhesives prepared in Examples 3-4
[0141]
[0142] Table 6 Performance data of cement adhesive prepared in Examples 3-4
[0143]
[0144] It can be seen from Tables 5-6 that under natural curing, the cement adhesive of the present invention has excellent mechanical properties.
[0145] The cement adhesive prepared in Examples 3 to 4 was poured into the anti-pollution porcelain insulator for high-cold areas, and then sequentially stopped for 4 hours, steamed at 50°C for 6 hours, and cured in standard constant temperature water for 28 days, and then tested according to standard DL / T 557-2021. The pass rate of the impact breakdown test was shown in Table 7.
[0146] Table 7 Performance data of the cement adhesive prepared in Examples 3-4 after curing
[0147]
[0148] It can be seen from Table 7 that the cement adhesive of the present invention has excellent electrical properties.
[0149] It can be seen from the above embodiments and comparative examples that the cement adhesive provided by the present invention can improve the electrical performance of the cement adhesive, ensuring that the porcelain insulator can still operate safely and stably when facing steep wave impulse voltage.
[0150] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A cement adhesive, characterized in that: It is composed of the following components: aluminate cement, artificial porcelain sand, microsilica powder, admixture and water; The external admixture includes carbon nanotubes, sodium chloride, a water reducing agent and a defoaming agent; The water reducer is a polycarboxylate water reducer; The mass of the carbon nanotubes is 0.03-0.05% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; The mass of the sodium chloride is 0.1-0.3% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; The preparation method of the cement adhesive is: Aluminate cement, artificial porcelain sand, microsilica powder, admixture and water are mixed to obtain cement adhesive; The cement adhesive is applied to anti-pollution porcelain insulators in high-cold areas.
2. The cement adhesive according to claim 1, characterized in that: The mass of the aluminate cement is 45-62% of the total mass of the aluminate cement, artificial porcelain sand and microsilica powder.
3. The cement adhesive according to claim 1, characterized in that: The mass of the artificial porcelain sand is 25~45% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder; the mass of the microsilica powder is 5~10% of the total mass of aluminate cement, artificial porcelain sand and microsilica powder.
4. The cement adhesive according to claim 1, characterized in that: The water-cement ratio of the cement adhesive is 0.20-0.
25.
5. The method for preparing the cement adhesive according to any one of claims 1 to 4, characterized in that: for: Aluminate cement, artificial porcelain sand, microsilica powder, admixtures and water are mixed to obtain cement adhesive.
6. Use of the cement adhesive according to any one of claims 1 to 4 or the cement adhesive prepared by the preparation method according to claim 5 in anti-pollution porcelain insulators in high-cold areas.
7. The use according to claim 6, characterized in that: The method of application includes: The cement adhesive is poured into the anti-pollution porcelain insulators in high-cold areas, and then static curing, steam curing and standard water curing are carried out in sequence.
8. The use according to claim 7, characterized in that: The static time is 4-5 hours; the steaming temperature is 45-55° C., and the steaming time is 5-6 hours.
Citation Information
Patent Citations
Cement adhesive as well as preparation method and application thereof
CN116425479A
Cement adhesive for quickly testing strength of porcelain insulator porcelain piece as well as preparation method and application of cement adhesive
CN117756484A